Antioxidant Activity Test of Caulerpa racemosa Extract from Takalar District Using the FRAP (Ferric Reducing Antioxidant Power) Method - Andi Ulfiana Utari; Nurhikma A; Eka Astuti (NSMRJ: Nusantara Scientific Medical Research Journal, 2023)
Sea grapes or Caulerpa racemosa contain alkaloids, flavonoids, tannins, phenols and steroids. These compositions work as antioxidants. Antioxidants are compounds that can contribute one or more electrons to free radicals, so that the free radicals can be suppressed. The goal of this study was to determine the antioxidant activity of sea grape (Caulerpa racemosa) extract using the FRAP method. Extraction of sea grapes (Caulerpa racemosa) applied maceration and methanol methods. Absorbance of antioxidant activity was measured using a UV-VIS spectrophotometer at a wavelength of 700 nm. The results showed that sea grape extract (Caulerpa racemosa) had an antioxidant activity of 152 mg AAE/g extract. It means that in each gram of extract, it is equivalent to 152 mg of ascorbic acid.